2016
DOI: 10.1037/sah0000024
|View full text |Cite
|
Sign up to set email alerts
|

The self-stigma process in criminal offenders.

Abstract: Upon conviction, individuals receive the stigmatizing label “criminal offender.” Existing stereotypes about criminal offenders may be integrated into the self-concept, a phenomenon known as self-stigma. In many stigmatized groups, self-stigma is a robust predictor of poor functioning (Livingston & Boyd, 2010; Schomerus et al., 2011). However, little is known about how self-stigma occurs (Corrigan et al., 2006), and there has been limited research with criminal offenders. This study examines a theoretical model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 60 publications
(117 reference statements)
7
53
0
Order By: Relevance
“…Upon release from jail or prison, blacks face greater stigma and discrimination relative to whites, which may affect employment and access to medical care. [47, 48]. This type of discrimination may affect the risk of post-release opioid-related overdose; however, post-release opioid-related overdose mortality is greater among whites released from jail or prison relative to blacks and other racial minorities [15, 16].…”
Section: Underlying Factors and Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon release from jail or prison, blacks face greater stigma and discrimination relative to whites, which may affect employment and access to medical care. [47, 48]. This type of discrimination may affect the risk of post-release opioid-related overdose; however, post-release opioid-related overdose mortality is greater among whites released from jail or prison relative to blacks and other racial minorities [15, 16].…”
Section: Underlying Factors and Settingmentioning
confidence: 99%
“…There are few groups as highly stigmatized as PRJP [69]. PRJP perceive high levels of stigma, which may lead them to internalize the stigma and ultimately self-stigmatize [47, 70]. Among PRJP in New York state, 65.3% reported discrimination due to their prior criminal justice involvement [71].…”
Section: Intermediate Determinantsmentioning
confidence: 99%
“…Providers’ lower level of regard for criminal justice–involved clients is consistent with prior research showing that individuals recently released from prison reported feeling subject to discrimination by health care workers (14). These negative attitudes may stem from the risk factors for criminal justice involvement, such as impulsive or aggressive behavior, that can make working with justice-involved clients a challenge; the negative attitudes may also represent an implicit bias, pervasive in U.S. society, against people with criminal records (15). Future research should elucidate how these differing attitudes by clients’ criminal justice status affect service delivery and care.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore took a broad approach to measuring rejection and included measures of both perceived discrimination and stigma towards ex‐prisoners. We measured perceived discrimination using an adapted version of the Perceptions of Discrimination Scale (Schmitt & Branscombe, ; 9 items used in Cruwys & Gunaseelan, ; α = 0.91), and measured perceived stigma using the 8‐item subscale from the Self‐Stigma of Individuals with Criminal Records scale (SSICR; Moore, Tangney, & Stuewig, ; α = 0.94). The discrimination scale assesses personal experiences and perceptions of discrimination, whereas the stigma scale assesses perceptions of the attitudes underlying discriminatory behavior.…”
Section: Methodsmentioning
confidence: 99%